2018
DOI: 10.15252/embj.201796553
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA and TLR9 drive muscle inflammation upon Opa1 deficiency

Abstract: Opa1 participates in inner mitochondrial membrane fusion and cristae morphogenesis. Here, we show that muscle-specific Opa1 ablation causes reduced muscle fiber size, dysfunctional mitochondria, enhanced Fgf21, and muscle inflammation characterized by NF-κB activation, and enhanced expression of pro-inflammatory genes. Chronic sodium salicylate treatment ameliorated muscle alterations and reduced the muscle expression of Fgf21. Muscle inflammation was an early event during the progression of the disease and oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
157
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(177 citation statements)
references
References 67 publications
3
157
0
Order By: Relevance
“…Moreover, the accumulation of the glial fibrillary acidic protein (GFAP) indicated neuroinflammation ( Fig 1D), which was further substantiated by the increased expression of the proinflammatory cytokines and NF-jB target genes Tnfa, Il-1b, Asc, and Myd88 in retinas of 6-week-old NYKO mice ( Fig 1E). These findings are reminiscent of inflammatory responses observed in muscular OPA1 deficiency (Rodriguez-Nuevo et al, 2018). Similar to this model, we observed increased expression of Fgf21 ( Fig 1F).…”
Section: Loss Of Yme1l In the Nervous System Causes Microphthalmia Csupporting
confidence: 86%
“…Moreover, the accumulation of the glial fibrillary acidic protein (GFAP) indicated neuroinflammation ( Fig 1D), which was further substantiated by the increased expression of the proinflammatory cytokines and NF-jB target genes Tnfa, Il-1b, Asc, and Myd88 in retinas of 6-week-old NYKO mice ( Fig 1E). These findings are reminiscent of inflammatory responses observed in muscular OPA1 deficiency (Rodriguez-Nuevo et al, 2018). Similar to this model, we observed increased expression of Fgf21 ( Fig 1F).…”
Section: Loss Of Yme1l In the Nervous System Causes Microphthalmia Csupporting
confidence: 86%
“…On one hand, FGF21 has gained attention for being a potential therapeutic protein for obesity and type 2 diabetes because it stimulates the oxidation of fatty acids, the production of ketone bodies, and inhibits lipogenesis . On the other hand, several reports indicate a pathophysiological role for FGF21: (i) it promotes bone loss and reduces bone mineral density; (ii) FGF21 is a stress‐induced myokine, which is released under conditions of starvation, ER stress, mitochondrial dysfunction, obesity, mitochondrial myopathies, and aging . We have recently shown that chronic elevation of muscle‐derived circulating FGF21 leads to systemic inflammation, precocious senescence, and premature death .…”
Section: Discussionmentioning
confidence: 99%
“…In skeletal muscle, FGF21 expression, in healthy conditions, is almost undetectable, and therefore, the circulating FGF21 is predominantly produced and released by the liver . In contrast, muscle‐dependent systemic release of FGF21 increases with starvation, endoplasmic reticulum stress, mitochondrial dysfunction, obesity, mitochondrial myopathies, and aging . Moreover, FGF21 is a stress‐induced myokine that has been proposed as a specific serum biomarker of muscle‐specific mitochondrial disorders .…”
Section: Introductionmentioning
confidence: 99%
“…96 This was cGASindependent and may have been TLRdependent. 96 Mitochondria in OPA1 knockdown cells appear more fragmented than the untreated cells 96 and may mimic the swing towards fission experienced during some microbial infections. Thus, some forms of mitochondrial disruption may deliver a TLR9-driven priming signal for the NLRP3 inflammasome.…”
Section: Tlr9 Senses Endosomal Cpg Dnamentioning
confidence: 98%
“…93 TLR9 recognises unmethylated CpG in the endosomal system, 94,95 including that of mitochondrial origin following mitochondrial disruption. [96][97][98][99] CpG recognition by TLR9 provides a signal 1 for NLRP3 activation, transcriptionally upregulating inflammasome-required genes under NF-jB control 100,101 (Figure 3b). The mitochondrial dynamics that drive disruption and exposure of mtDNA to TLR9 are varied and unclear, yet some evidence implicates defective fission/fusion dynamics.…”
Section: Tlr9 Senses Endosomal Cpg Dnamentioning
confidence: 99%